Pathoproteomic profiling of the skeletal muscle matrisome in dystrophinopathy associated myofibrosis. Issue 2 (7th September 2015) - Holland, Ashling; Murphy, Sandra; Dowling, Paul; Ohlendieck, Kay
Abstract : The gradual accumulation of collagen and associated proteins of the extracellular matrix is a crucial myopathological parameter of many neuromuscular disorders. Progressive tissue damage and fibrosis play a key pathobiochemical role in the dysregulation of contractile functions and often correlates with poor motor outcome in muscular dystrophies. Following a brief introduction into the role of the extracellular matrix in skeletal muscles, we review here the proteomic profiling of myofibrosis and its intrinsic role in X‐linked muscular dystrophy. Although Duchenne muscular dystrophy is primarily a disease of the membrane cytoskeleton, one of its most striking histopathological features is a hyperactive connective tissue and tissue scarring. We outline the identification of novel factors involved in the modulation of the extracellular matrix in muscular dystrophy, such as matricellular proteins. The establishment of novel proteomic markers will be helpful in improving the diagnosis, prognosis, and therapy monitoring in relation to fibrotic substitution of contractile tissue. In the future, the prevention of fibrosis will be crucial for providing optimum conditions to apply novel pharmacological treatments, as well as establish cell‐based approaches or gene therapeutic interventions. The elimination of secondary abnormalities in the matrisome promises to reduce tissue scarring and the loss of skeletal muscle elasticity.